Short-term venom immunotherapy induces desensitization of FcεRI-mediated basophil response - Čelesnik, N.; Vesel, T.; Rijavec, M.; Šilar, M.; Eržen, R.; Košnik, M.; Kloft Žitnik, S. E.; Avčin, T.; Korošec, P. (Allergy (Copenhagen), 2012)
Background The precise immunological mechanisms for the early clinical protection of venom immunotherapy (VIT) have not yet been explained. Our aim was to evaluate whether high‐affinity IgE receptor (FcεRI) and the related basophil function have a role in the induction of short‐term VIT protection. Methods We included 60 adults and 48 children. Basophil threshold sensitivity (CD‐sens) to anti‐FcεRI stimulation, and FcεRI gene and cell‐surface expression were assessed at the beginning and just before the first maintenance dose (MD) of 100 μg of ultra‐rush VIT (day 5) and at the beginning, during buildup, and just before the first MD of 70 μg and of 100 μg of semi‐rush VIT (weeks 1–2 and 5). Results We demonstrated a significant reduction in CD‐sens to anti‐FcεRI stimulation before the first MD in both ultra‐rush and semi‐rush VIT in all included subjects. FcεRI gene and/or cell‐surface expression was decreased in 34–100% of subjects, with different dynamics between VIT protocols. Conclusion We found a marked desensitization of FcεRI‐activated basophils after short‐term VIT. This suppression, which could be highly relevant for the development of early protective mechanisms, might be also related to the changes at the level of FcεRI expression.